(untitled) (REMUNOM, 2024)
The technological and quality development of medicines must follow several quality standards to ensure that a given drug has its pharmacological activity demonstrated. Among the medicines sold is Zolpidem Hemitartrate, which belongs to the imidazopyridine class and is used in the treatment of insomnia. The coated tablets must comply with quality control criteria such as: dosage, hardness, average weight, disintegration and dissolution. The objective of this study was to evaluate the quality of Zolpidem Hemitartrate tablets sold in Itacoatiara through pharmacopoeial tests. The tests were carried out at UFAM in Itacoatiara and Fametro in Manaus. The results obtained presented values ​​within what is established by the Brazilian Pharmacopoeia.